2023
DOI: 10.14336/ad.2022.0424
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for One-Year Mortality in Hospitalized Adults with Severe COVID-19

Abstract: As the body's immunity declines with age, elderly-hospitalized patients due to COVID-19 might be at higher mortality risk. Therefore, the aim of this prospective study was to examine the possible risk factors (demographic, social or comorbidities) most associated with mortality one-year after diagnosis of COVID-19. Routine data were collected from a cohort of hospitalized adults with severe COVID-19. The primary endpoint was mortality at one-year after diagnosis of COVID-19. We used a Cox proportional hazard m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…Low socioeconomic status after bariatric surgery was also associated independently and significantly with increased susceptibility to SARS-CoV-2 infection, in agreement with previous publications of this risk factor in the general population [3,8,10,44]. We found that physical activity after bariatric surgery of at least three times a week was associated with a significantly reduced odd of SARS-CoV-2 infection, as observed in the general population regarding the rates [45] and severity [46,47] of SARS-CoV-2 infection.…”
Section: Discussion Of the New Findingssupporting
confidence: 91%
“…Low socioeconomic status after bariatric surgery was also associated independently and significantly with increased susceptibility to SARS-CoV-2 infection, in agreement with previous publications of this risk factor in the general population [3,8,10,44]. We found that physical activity after bariatric surgery of at least three times a week was associated with a significantly reduced odd of SARS-CoV-2 infection, as observed in the general population regarding the rates [45] and severity [46,47] of SARS-CoV-2 infection.…”
Section: Discussion Of the New Findingssupporting
confidence: 91%
“…Another study found that age and FR were independently associated with adverse outcomes in COVID-19 patients, and patients that survived had more care requirements than non-FR or younger patients [ 37 ]. Another study in a cohort of 368 COVID-19 patients found that age was independently associated with 1-year mortality [ 53 ]. In our study we have not found independent associations of age with mortality, however, we only included patients above 70 years old and inside this age group, mortality was associated with other factors such as functionality, nutrition and swallowing function.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these findings are consistent with those of previous studies of the in-hospital mortality of elderly patients with COVID-19 ( 14 , 16 , 24-27 ). Among studies in the general population, age has been reported as an independent predictor of mortality within 1 year after COVID-19 ( 28 , 29 ). It has also been reported that in the general population, chronic obstructive pulmonary disease, chronic cardiovascular disease and active malignancy are also independent predictors of 1-year mortality following infection with SARS-CoV-2( 29 ).…”
Section: Discussionmentioning
confidence: 99%